Analisis Muatan Karakter Pada Pelajaran Pjok Kelas VI Semester II Di SDN 1 Batu Kumbung 2020/2021 - Aprianto, M. Kadirun; Safruddin, Safruddin; Jaelani, Abdul Kadir (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This study aimed to describe the character education contents in physical education, sports, and health subject for 2nd semester of 6th grade at SDN 1 Batu Kumbung. This research was qualitative research. The data collection techniques used in this study were interviews, documentation, and observation. The data has been collected analyzed using an interactive analysis model from Miles, Huberman, and Saldana, i.e. condensation data, presentation data, and conclusing data. As the result, this study revealed that 1) character education contents instilled in physical education, sports, and health implementation learning are independent, like to read, and curiousity. 2) character education contents instilled in physical education, sports, and health evaluation learning are honest, independent, and hard working, 3) character education contents instilled in physical education, sports, and health materials learning are hard working, independent, social caring, and discipline.